Opportunities to learn ambitious mathematics teaching from co-planning instruction - Fauskanger, Janne; Bjuland, Raymond (NOMAD Nordic Studies in Mathematics Education, 2021)
This study explores ambitious teaching practices teachers have opportunities to learn when co-planning instruction as part of their professional development. An analytical framework associated with Sociocultural discourse analysis is applied to identify utterances (dialogue moves) in the co-planning sessions that are essential in helping the teachers to develop their reasoning together. The findings reveal that the participants work on the ambitious practices of predicting student responses, representing these responses and aiming towards the goal for the lesson when co-planning to introduce the distributive property of multiplication to their students. Dialogue moves in the reasoned dialogues such as expressing shared ideas and agreements, providing arguments and challenging each other’s ideas are found to be essential for providing the teachers with opportunities to learn to predict student responses, to represent these responses and to aim towards the learning goal for the lesson.